Malaysian Lesbian’s Stress Level - S.M, Zhooriyati; Hashim, Intan H.M (HUMANITAS, 2014)
ABSTRACTThis research focuses on Pengkid. It is a term or a slang used in Malaysia to refer to lesbians in the butch category. They are a group of individuals who are having non-traditional sexual orientation,in which they are sexually attracted to biologically-defined women. This research was conducted in order to focus on their sources and level of stress and a semi-structured interview schedule wasadministered with 25 pengkid participants from Pulau Pinang, Kuala Lumpur and Selangor. Participants were recruited through various methods including from Malaysian Pengkid official website and snowballing technique.Various challenges related to day-to-day life were reported by participants. However, financial problems, conflicts in work place or study place and conflictswith girlfriends have been identified as their main sources of stress. Since they are supporting families, girlfriends and themselves, they face financial problems almost every month. At the same time, having more expenses compared to their income also caused this problem. Findings show that Malaysian Pengkid does not face any kind of problems or stress because of their identity. Malaysia’s Pengkid seems to face the same problem that is faced by people with traditional sexual orientation and. They also do not have critical stress level and it is still manageable.Keywords: pengkid, lesbian, stress, life challenges